1991
DOI: 10.1002/bip.360310810
|View full text |Cite
|
Sign up to set email alerts
|

Information concerning the mechanism of electrophoretic DNA separation provided by quantitative video‐epifluorescence microscopy

Abstract: Changes in conformation, length, and mobility of individual DNA molecules during agarose gel electrophoresis were measured using video micrographs obtained by epifluorescence microscopy. Globular, V-shaped, and linear conformations of DNA are found. The mobility, upon transformation from the globular to the V-shaped conformation, decreases, suggesting a collision with a gel fiber. The duration of interaction between DNA and gel fiber is proportional to the length of DNA. Hypothetically, this proportionality un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 18 publications
2
19
0
Order By: Relevance
“…Band spacing in agarose gels has been investigated both theoretically [8-111 and experimentally [13]; however, factors affecting the band width have not been investigated quantitatively. In this study, we adopted the rep-…”
Section: Discussionmentioning
confidence: 99%
“…Band spacing in agarose gels has been investigated both theoretically [8-111 and experimentally [13]; however, factors affecting the band width have not been investigated quantitatively. In this study, we adopted the rep-…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence videomicroscopy studies have suggested that large DNA molecules become hooked around obstacles in the agarose gel matrix during electrophoresis, leading to U-shaped conformations with the arms of the “U” pointing in the direction of the electric field [59-64]. Eventually, one of the arms of the “U” slides off the obstacle and the DNA collapses into a globular shape, before beginning the stretching and hooking process again [60-63].…”
Section: Agarose Gelsmentioning
confidence: 99%
“…Eventually, one of the arms of the “U” slides off the obstacle and the DNA collapses into a globular shape, before beginning the stretching and hooking process again [60-63]. Since the duration of interaction between DNA and the gel fibers is proportional to DNA length [64], DNA mobilities appear to be determined in part by interactions between the DNA molecules and the agarose gel matrix. Agarose fibers are known to bind anions [65], some of which appear to be localized near the junction zones [66].…”
Section: Agarose Gelsmentioning
confidence: 99%
“…It can now be directly observed by fluorescence videomicroscopy. 12 We show in this paper that the measurements of the overall average of the orientation over many chains, as deduced from dichroism or birefringence, allows to very quantitatively characterize the relative importance of "stretching" and "overstretching" and of their respective dynamics. This characterization relies on the design of an instrument with very high signalto-noise ratio and use of convenient shape to which the birefringence decay can be fitted as described in Materials and Methods.…”
Section: Introductionmentioning
confidence: 99%